ESTABLISH COMMUNICATION METHODOLOGY - Aziza Jorayeva (Journal of new century innovations, 2022)
Annotation: In this article, the communication relationship between people, considered the main category of pedagogical-psychological sciences, the teacher should be attentive to the student in the process of communication, it is written that he should carefully study his psychological condition and then give him reprimands or warnings. Also, the principles of communication between the teacher and the student are discussed separately. Various negative consequences occur in the student due to the teacher's incorrect communication with the student, as a solution to this, the recommendations needed by the teacher are given. At the end of the article, it is written in detail about the requirements of the teacher to the student in the process of education.